축산물위해요소 정보인식이 식품소비에 미치는 영향 분석 - 황윤재 (한국농촌경제연구원, 2011)
Information is an important factor in forming awareness on hazard factors. The purpose of this study is to analyze the role of consumers' information awareness affecting the relationship between livestock products hazard factors and food consumption. This study conducted a random survey of 343 housewives around the capital area to accomplish the objective of the study. The livestock products hazard factors included in this study were three animal diseases: bovine spongiform encephalopathy (BSE), foot-and-mouth disease (FMD), and avian influenza (AI). An econometrics model of binary logit for each animal disease was introduced for the analysis. The results show that common information aspects which affect the relationship between food consumption and animal products hazard factors are consumers' interest on and needs for food safety information. Also, the variable on consumers' preference of acquiring source for food safety information was significant for all models. However, the variables of consumers' satisfaction on food safety information and awareness for the mass distribution problem of food safety information among consumers were only significant for BSE model. Besides information factors, the estimation results show that consumers' preference for beef has significant effect for BSE and FMD models. Consumers' awareness on food safety of domestic or imported animal products and their residence area were significant for all three models.
Keywords: 가축질병; 축산물위해요소; 식품안전정보; 광우병; 구제역; 조류인플루엔자; animal disease; animal products hazard factors; food safety information; bovine spongiform encephalopathy; foot-and-mouth disease; avian influenza